Implication of Oncogenic Signaling Pathways as a Treatment Strategy for Neurodegenerative Disorders - Contemporary Approaches - Sieradzki, Adrian; B. Yendluri, Bharat; H. Palacios, Hector; Parvathaneni, Kalpana; Prakash Reddy, V.; E. Obrenovich, Mark; Gasiorowski, Kazimierz; Leszek, Jerzy; Aliev, Gjumrakch (CNS & Neurological Disorders - Drug Targets, 2011)
Recent evidence has associated the aberrant, proximal re-expression of various cell cycle control elements with neuronal cell vulnerability in Alzheimer's and Parkinson's diseases, as a common chronic neurodegeneration. This phenomenon associated with oncogenic transduction pathways activation has attracted the interest of scientists all over the world for a few years now. The purpose of this paper is to outline areas of research related to oncogenic factors or medicines in the context of potential applications for future treatment of the above mentioned chronic and, largely, incurable diseases.
Keywords: mitochondria